Eye tracker as a pro-social tool of managing urbanistic and architectural heritage - Rusnak, Marta Alina (Protection of Cultural Heritage, 2020)
The subjective point of view of experts is often translated into attempts at free reinterpretation of legal acts. The participants of the " dispute about a monument" may include the investor, architect, conservators, politicians, officials, as well as third parties - citizens. In order to make it possible to objectivize the decisions made, to establish a dialogue based on a common point of reference or to give the public the opportunity to object, I suggest performing oculographic examinations. Eye tracking (or oculography) allows to track how people become visually familiar with the objects presented to them. By registering the movements of eyeballs of a large group of observers, it is possible to examine the preferences governing this process as well as to observe the changes resulting from modifications introduced within the presented object. The article briefly discusses the possible use of eye trackers for the purposes of diverse legal protection of historical monuments and a multifaceted opportunity for the society to participate in this process. The text also includes arguments for and against the introduction of such a method to common use. For the legibility of the argument, the phenomenon is described based on the example of the library erected in Ostrów Tumski in Wrocław. The aim of the article is not to undertake an individual criticism of the mentioned realization, but only to list the problems that could be efficiently solved thanks to a completely new research approach.